Enrichment of Sawahlunto Clay with Cation Ca2+ and Cu2+ and Preliminary Test of its Catalytic Activity in CPO Transesterification Reaction - Lestari Ningsih; Aju Deska; Syukri Arief; Upita Septiani; Yulia Eka Putri; Mai Efdi; . Syukri (Aceh International Journal of Science and Technology, 2020)
This research is aimed to examine the catalytic activity of Sawahlunto clay, which is enriched with Ca2+ and Cu2+ transesterification of Crude Palm Oil (CPO) to produce biodiesel. Based on the results of the analysis with X-Ray Fluorescence (XRF) and X-Ray Diffraction (XRD), Sawahlunto clay consists of about 61% Si and 24% Al with a Si/Al mole ratio of 2.7 and typical clay mineral consisting of kaolinite and illite, another mineral fund was quartz and goethite. The mineral composition changes after calcination, where kaolinite and illite disappeared. Fourier Transform Infrared (FTIR) analysis shows that calcination can remove the organic compounds Sawahlunto clay; thus, the clay was used without calcination for the next step. Clay samples can be enriched with Ca2+ ions and Cu2+ ions without damaging their mineral composition, where more Cu2+ ions are loaded than Ca2+ ions. The Sawahlunto clay enriched with Ca2+ ions showed a slightly better catalytic activity in the transesterification of crude palm oil (CPO) than its parent clay; when enriched with Cu2+ ions, the catalytic activity did not appear at all. However, the homogeneous counterpart of such catalyst, calcium nitrate, was still the most active and selective compared to all others